Antifouling and desalination enhancement of forward osmosis-based thin film composite membranes via functionalized Multiwalled carbon nanotubes mixed matrix Polyethersulfone substrate - E. Almansouri, Hamza; Edokali, Mohamed; Mazrul Nizam, Abu Seman; Ntone, Ellora Priscille Ndia; Che Ku Mohammad Faizal, Che Ku Yahya; Mohammad, Abdul Wahab (MDPI, 2025)
The growing scarcity of freshwater worldwide has increased interest in forward osmosis (FO) membranes as a promising solution for water desalination and wastewater treatment. This study investigates the enhancement of thin-film composite (TFC) FO membranes via the incorporation of carboxyl-functionalized multiwalled carbon nanotubes (COOH-MWCNTs) into the polyethersulfone (PES) support layer. The membranes were fabricated using a combination of phase inversion and interfacial polymerization techniques, with COOH-MWCNTs incorporated into the membrane support layers at different concentrations (0–0.75 wt.%). Comprehensive characterization was carried out using various analytical methods and mechanical testing to evaluate the physicochemical and structural properties of the membranes. The modified membranes demonstrated improved hydrophilicity, enhanced mechanical and thermal stability, and improved surface charge properties. Performance tests using a 1 M NaCl draw solution showed that the optimized membrane (0.5 wt.% COOH-MWCNTs) attained a 161% enhancement in water flux (7.48 LMH) compared to the unmodified membrane (2.86 LMH), while also reducing internal concentration polarization (ICP). The antifouling properties were also significantly improved, with a flux recovery rate of 91.92%, attributed to enhanced electrostatic repulsion as well as surface and microstructural modifications. Despite a moderate rise in reverse solute flux, the specific reverse solute flux (Js/Jw) remained within acceptable limits. These findings highlight the potential of COOH-MWCNT-modified membranes in enhancing FO desalination performance, offering a promising option for next-generation water purification technologies.